Pengaruh Keamanan, Kualitas Informasi dan Kemudahan terhadap Keputusan Pembelian Online pada Konsumen Tiktok Shop - Nurmalasari, Nurmalasari; Latifah, Latifah (www.bsi.ac.id, 2023)
This study is entitled the effect of security, information quality and convenience on online purchasing decisions for tiktok shop consumers which aims to determine how security, information quality and convenience affect online purchasing decisions partially or simultaneously. The data collection method used is the simple random sampling method, namely people who have shopped at tiktokshop. Data collection using a questionnaire, namely by distributing a list of questions using Google Form to respondents randomly to tiktok users. The number of samples taken based on the responses to the incoming questionnaire responses was 148 respondents. Furthermore, the results of the respondents' responses were tabulated and tested for feasibility. The research model that will be used in this study is a regression analysis model to test the proposed hypothesis using Multiple Linear Regression techniques using the SPSS 25.0 programme. The results showed that online purchasing decisions were simultaneously and partially influenced by the variables of security, information quality and ease of tiktok shop consumers in shopping. Keywords: purchase, online, tiktok shop